Just watching the game ain't enough: striatal fMRI reward responses to successes and failures in a video game during active and vicarious playing - Kätsyri, Jari; Hari, Riitta; Ravaja, Niklas; Nummenmaa, Lauri (Frontiers in Human Neuroscience, 2013)
Although the multimodal stimulation provided by modern audiovisual video games is pleasing by itself, the rewarding nature of video game playing depends critically also on the players’ active engagement in the gameplay. The extent to which active engagement influences dopaminergic brain reward circuit responses remains unsettled. Here we show that striatal reward circuit responses elicited by successes (wins) and failures (losses) in a video game are stronger during active than vicarious gameplay. Eleven healthy males both played a competitive first-person tank shooter game (active playing) and watched a pre-recorded gameplay video (vicarious playing) while their hemodynamic brain activation was measured with 3-tesla functional magnetic resonance imaging (fMRI). Wins and losses were paired with symmetrical monetary rewards and punishments during active and vicarious playing so that the external reward context remained identical during both conditions. Brain activation was stronger in the orbitomedial prefrontal cortex (omPFC) during winning than losing, both during active and vicarious playing conditions. In contrast, both wins and losses suppressed activations in the midbrain and striatum during active playing; however, the striatal suppression, particularly in the anterior putamen, was more pronounced during loss than win events. Sensorimotor confounds related to joystick movements did not account for the results. Self-ratings indicated losing to be more unpleasant during active than vicarious playing. Our findings demonstrate striatum to be selectively sensitive to self-acquired rewards, in contrast to frontal components of the reward circuit that process both self-acquired and passively received rewards. We propose that the striatal responses to repeated acquisition of rewards that are contingent on game related successes contribute to the motivational pull of video-game playing.